PENGARUH PROFITABILITAS, LIKUIDITAS, DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL (Studi Empiris Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Periode 2020-2022) - Nur, Rahmaniyah Nur Safitri; Suhendro; Agni Astungkara (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
The research is intended to analyze capital structure whether or not it is influence by profitabilit, liquidity, and company size of manufacturing companies in the consumer goods industry sector on the Indonesia Stock Exchange for the 2020-2022 period. The study was carried out by analyzing secondary data throught the company’s annual report. This study utilized purposive sampling based on sample determination so that 35 companies were obtained. The technique applied in the analysis is multiple linear regression. Findings from the research reveal that capital structure is significantly influenced by profitability and liquidity, but capital structure is not significantly influenced by company size.